A chemically amplified molecular glass resist with an ionic photoacid generator and a single protection group. Issue 2 (2nd August 2013) - Kasai, Tatsuaki; Higashihara, Tomoya; Ueda, Mitsuru
ABSTRACT A molecular glass resist with an ionic photoacid generator and a single protection group (MR‐1) has been developed. MR‐1 exhibited good thermal properties, such as a 5% weight loss temperature (Td5%) of 167°C and a glass transition temperature (Tg) of 80°C. MR‐1 showed the good sensitivity of 80 μC/cm2 and high contrast of 4.9 with e‐beam exposure (50 keV). A relatively high resolution of 50 nm and low Line‐Edge‐Roughness of 3.8 nm were obtained by e‐beam exposure (100 keV). © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39769.